Secondary metabolites of Alternaria: A comprehensive review of chemical diversity and pharmacological properties - Zhao, Shiqin; Li, Juan; Liu, Jinping; Xiao, Shaoyujia; Yang, Sumei; Mei, Jiahui; Ren, Mengyao; Wu, Shuzhe; Zhang, Hongyuan; Yang, Xiliang (Frontiers in Microbiology, 2023)
Fungi are considered to be one of the wealthiest sources of bio-metabolites that can be employed for yielding novel biomedical agents. Alternaria, including parasitic, saprophytic, and endophytic species, is a kind of dark fungi that can produce a broad array of secondary metabolites (SMs) widely distributed in many ecosystems. These are categorized into polyketides, nitrogen-containing compounds, quinones, terpenes, and others based on the unique structural features of the metabolites. New natural products derived from Alternaria exhibit excellent bioactivities characterized by antibacterial, antitumor, antioxidative, phytotoxic, and enzyme inhibitory properties. Thus, the bio-metabolites of Alternaria species are significantly meaningful for pharmaceutical, industrial, biotechnological, and medicinal applications. To update the catalog of secondary metabolites synthesized by Alternaria fungi, 216 newly described metabolites isolated from Alternaria fungi were summarized with their diverse chemical structures, pharmacological activity, and possible biosynthetic pathway. In addition, possible insights, avenues, and challenges for future research and development of Alternaria are discussed.